PENGARUH PENGAWETAN VENIR DENGAN SENYAWA BFCA TERHADAP KETEGUHAN REKAT KAYU LAPIS DARI KAYU KARET (Hevea brasiliensis) - Suwandi Kliwon; M I lskandar; Paribotro Sugitno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
This paper describes the treatment of 1.5 mm x 20 cm x 20 cm rubberwood veneer with BFCA compound of 5 %, 10%. 15 %, 20 % and control, and 3 variations of extender in urea formaldehyde glue , compositionic 10%, 20% and 30%.The results reveal that the concentration of BFCA influences the bonding strength of rubberwood plywood using Indonesian standard. On the other hand the effect of percentage of extender in tne compostion of urea formal dehyde glue is not significant on the bonding strength using Indonesian and Japanese standard. But the interaction. of concentration of BFCA and percentage of extender influences the bonding strength of plywood.